The involvement of private agents in the supervisory activity in the peruvian power sector: a brief approach to its study - Zegarra Valdivia, Diego (2016)
One of the most relevant powers available for the Public Administration so it is able to meet its objectives is the supervisory power. However, this is a matter insufficiently studied in the national legal ambit. In this article, the author conceptualizes the legal figure of supervision, proposing that it is a synonym of “inspection” and other similar concepts, and that it has wider purposes than the ones established in the Peruvian administrative legislation (that tends only to subsume it into the sanctioning power). With this theoretical framework, the author briefly analyses the phenomenon of the delegation of this power in the Peruvian power sector.